A cross-sectional study of Colombian University students’ self-perceived lifestyle (2015)
Background: The Fantastic Lifestyle Questionnaire was designed for enabling staff working in health sciences and physical activity (PA) areas to measure lifestyles (LS) in the general population. The aim of this study was to assess the lifestyle in a sample of university students. Method: This was a cross-sectional, descriptive, observational study involving 5,921 subjects’ aged 18- to 30-years-old (3,471 females) from three Colombian cities. Was applied “Fantastic” instrument (that consists of 25 closed items on the lifestyle), translated to Spanish in versions of three and five answers. Results: Having a “good LS” was perceived by 57.4% of the females and 58.5% of the males; 14.0% of the females rating their LS as being “excellent” and males 19.3% (p  less than  0.001); 20.3% of the females and 36.6% of the males stated that they spent more than 20 min/day on PA (involving four or more times per week). Negative correlations between FANTASTIC score and weight (r = ?0.113; p  less than  0.01), body mass index (BMI) (r = ?0.152; p  less than  0.01) and waist circumference (r = ?0.178, p  less than  0.01) were observed regarding females, whilst the correlation concerning males was (r = ?0.143, p  less than  0.05) between Fantastic score and weight, (r = ?0.167 for BMI, p  less than  0.01) and (r = ?0.175, p  less than  0.01 for diastolic blood pressure). In spite of the students being evaluated referring to themselves as having a healthy LS (i.e. giving a self-perceived view of their LS), stated behaviour involving a health risk was observed in the domains concerning nutrition, PA and smoking. Conclusion: Specific diffusion, education and intervention action is thus suggested for motivating the adoption of healthy LS. © 2015, Ramírez-Vélez et al.